An improved empirical nonlinear model for InP-based HEMTs. (February 2020) - Zhong, Yinghui; Wang, Wenbin; Yang, Jie; Sun, Shuxiang; Chang, Mingming; Duan, Zhiyong; Jin, Zhi; Ding, Peng
Highlight: An improved model with better fitting accuracy in DC and RF characteristics. Improvement of output current model by introducing a variable knee voltage. Improvement of gate-charge model over a wide bias range by a piecewise function. Abstract: In this paper, an improved nonlinear model is proposed for self-developed on wafer InAlAs/InGaAs InP-based high election mobility transistors (HEMTs) over a wide operating bias range based on EEHEMT model, including non-linear channel current model and gate charge model. Actually, the knee voltage (Vsat ) increases linearly with gate-source voltage (VGS ) and finally approaches to saturation with the finite Si-doping density. Thereby, a hyperbolic tangent function (tanh) is used to describe the changing relationship, rather than idealized into a constant value with gate bias. Besides, a piecewise function is constructed to depict the variation of gate capacitance with bias voltage. Specifically, a third-order formula is utilized to accurately and simply characterize the downswing trend of gate capacitance with channel carrier density, which behaves as an effective extension of gate charge model at relatively large gate-source bias. Therefore, the improved model has shown a better accuracy between simulated and measured data with smaller error factor in output current, S-parameters, stability factor and frequency characteristics. The accurate and suitable empirical nonlinear model for InP-based HEMTs would be of great significance on design of high-frequency nonlinear circuits.